RELATIONSHIP OF SCREEN HOURS WITH DIGITAL EYE STRAIN: A CROSS SECTIONAL SURVEY FROM TEENAGERS - Maroof, Saira; Mashhadi, Syed Fawad; Azam, Naila; Haider, Kamran; Arshad, Nadia; Zulfiqar, Sundus; Mehboob, Qamar; Khalid, Saad; Ahmed, Safeer (Pakistan Armed Forces Medical Journal, 2019)
Objective:To determine the frequency of digital eye strain among teenagers and its association with screen hours.Study Design: Descriptive cross sectional survey. Place and Duration of Study: Government College Rawalpindi, from Sep 2016 to Mar 2017.Material and Methods:Three hundred eighty five teenagers (13-19 years) from a government college Rawalpindi were interviewed using a validated structured questionnaire. Data was collected about duration of computers, laptops or smart phone use and various related ocular and extra ocular symptoms. SPSS version 20 was used for data entry and analysis.Results:Mean age of the participant’s was 14.9 ± 1.99 years while mean hours of computer, laptop or smart screen use was 2.45 ± 1.49 hours. The most frequently experienced symptoms were headache 47.3%, followed by tired eyes 33.7%, blurred vision 25%, eye strain 22.3%, lightning or glare discomfort 20.5%, irritated or sore eyes 15% and dry eyes reported by 9.6% participants. There was a statistically significant relationship between Digital Eye Strain and screen hours (p